Perancangan Desain User Interface Pada Website Alumni Universitas Dinamika Untuk Meningkatkan Usability Dengan Menggunakan Metode User Centered Design - Safitri, Hanifah Lazuardy Eka; Sagirani, Tri; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
In Dinamika University exists an alumni’s website at http://alumni.dinamika.ac.id. According to an interview with the PLKA (Pusat Layanan Karir dan Alumni) division and other alumnis of the Dinamika University, it is found that the Alumni website is not fulfilling the needs of its user. From there, it is deduced that the main problems faced on this project is how to design the user interface on the Dinamika University’s Alumni website for increased usability with the UCD approach. In the UCD method, early and final evaluation of the design is carried on using heuristic evaluation with a severity rating scale ranging from 0 to 4, from the early design evaluation it is revealed that the old UI has problems of Catastrophic severity, which warrants a design adjustments and repairs. The designing process utilizes wireframes, storyboards, and prototypes. The general base and data for the designing process is gained from surveys of the PLKA and the alumnis, from which this design would later be subjected to a final evaluation to find out any usability problems, which using the same rating scale, is the rounded severity scale of 0, meaning that already fulfilling the need